Critical Aspects in Assessing Palliative End-of-Life Care: A Narrative Review of Family Support and Spiritual Needs - Ni Luh Putu Inca Buntari Agustini; Israfil Israfil; I Gede Putu Darma Suyasa; Untung Sujianto (Faculty of Nursing, Universitas Hasanuddin, 2026)
Aims: To review the existing evidence on the assessment of spiritual needs and family support in palliative end-of-life nursing care. Methods: A narrative review was conducted using databases, including ScienceDirect, EBSCOhost, ProQuest, and PubMed. Keywords included “palliative care,” “assessment tools,” “family,” and “spiritual.” After applying the inclusion criteria, 12 relevant articles were analyzed. Results: Two major assessment domains were identified. First, spiritual needs encompass perceptions of death, hopelessness, dependency, fear, avoidance, anxiety, stress, depression, Quality of Life (QoL), and religious barriers. Second, family support includes caregiver burden, fatigue, depression, declining physical health, anxiety, and financial stress. These factors influence both patient well-being and the family’s capacity to provide end of life care. Conclusion: Spiritual needs and family support are interconnected and critical components of a comprehensive palliative nursing assessment. Integrating structured spiritual and family assessment tools into clinical practice is essential for developing culturally sensitive holistic care plans that enhance quality of life and death. Future nursing education, clinical training, and policies should prioritize systematic assessment approaches and interdisciplinary collaboration to strengthen end-of-life care.